Aplikasi Teknik Rekayasa Genetik dalam Perbaikan Sumber Daya Genetik Tanaman untuk Ketahanan Cekaman Biotik - M. Herman (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2010)
The main constraint encountered in theutilization of plant genetic resources (PGR) in agriculture arebiotic stresses such as insect pests, plant diseases, and plantparasitic nematodes. The application of genetic engineeringtechniques create a great opportunity for crops improvementsparticularly for insect and plant diseases resistance. Throughgenetic engineering, genetically engineered (GE) crops havebeen developed, of which having the new traits such as resistanceto insect pests, plant diseases, and herbicide tolerance.GE crops are already widely grown and marketed in manycountries. Globally, GE crops that are commercialized consistsof four categories of traits, which are insect resistance (IR),herbicide tolerance, (HT), the combined traits of IR and HT(stacked genes), and virus resistance. Initially, GE crops hadbeen commercialized globally covering 1.7 million ha in 1996,and the cropping area increased rapidly to reach about 134million ha in 2009. Indonesia is known as a country rich inPGR, that have very high value. One of environmentallyfriendly technologies that can be applied in the utilization ofPGR in Indonesia, is genetic engineering. In Indonesia,research on plant genetic engineering had started since 1997.Commodities that are being researched to develop GE plantslimited on rice, potatoes and tomatoes. GE rice resistant tostem borer (Scirpophaga incertulas), GE potato resistant tolate blight (Phytophthora infestans), and GE tomato resistantto tomato yellow leaf curl virus (TYLCV) and cucumbermosaic virus (CMV) have been successfully developed byResearch Center for Biotechnology of Indonesian Institute ofScience and Indonesian Center for Agricultural Biotechnologyand Genetic Resources Research and Development(ICABIOGRAD). Those GE crops have been tested for theirresistance at the screenhouses, green houses of the biosafetycontainment, and confined field trial.